HISTORY AND APPLICATIONS OF PI (π) - Dr. David Rosangliana (International Educational Journal of Science and Engineering, 2024)
The ratio of the circumference to the diameter of a circle is represented by the irrational number pi (π). Pi was discovered and calculated thousands of years ago. It is widely used in mathematics and has a lot of practical uses. Although many individuals are familiar with the approximations of Pi (π) and its use in various formulas and theorems, they are unaware of its beauty and potential uses. The goal of the paper is to demonstrate Pi’s (π) elegance and practical uses.